Technological properties of wood of four species in the Amazonia - Medeiros, Dayane Targino de; Melo, Rafael Rodolfo de; Cademartori, Pedro Henrique Gonzalez de; Batista, Felipe Gomes; Mascarenhas, Adriano Reis Prazeres (Instituto de Ecología, A.C., 2021)
The work aimed to evaluate the technological properties of the wood from four species of Amazonia. Samples of timborana (Piptadenia suaveolens), pequiá (Caryocar villosum), sucupira (Bowdichia nitida) and maçaranduba (Manilkara huberi) were made. The wood was evaluated for their chemical constitution, physical properties (density, porosity, shrinkage and moisture content) and surface properties (color, NIR spectroscopy and wettability). The highest percentage of holocellulose, extracts and ashes were obtained in the pequiá wood. It was observed that the maçaranduba and sucupira were the densest. In timborana wood the greatest dimensional stability was registered. In the surface properties, the woods presented the colors: pinkish-gray (timborana), yellowish olive (pequiá), olive (sucupira) and dark brown (maçaranduba). The NIR spectra of the four species were similar, with little variation in the radial to the transversal plane. Regarding wettability, there was a reduction in the water contact angle from 5s to 10s, in both wood and planes.